Postmenopausal osteoporosis: Effect of moderate-intensity treadmill exercise on bone proteomics in ovariectomized rats - Yang, Yong-Jie; Li, Ye; Gao, Li (Frontiers in Surgery, 2023)
Objectives: This study aimed to identify the key proteins in the bone mass of ovariectomized (OVX) rats after a period of regular moderate-intensity treadmill exercise and to investigate their effects using tag mass spectrometry and quantitative proteomics with a view to improving the understanding and treatment of postmenopausal osteoporosis. Methods: Sixty three-month-old female Sprague-Dawley tats of specific-pathogen-free grade were randomly and equally divided into a sham operation group, ovariectomized group (OVX) and ovariectomized combined exercise (OVX+EX) group, and the latter took moderate-intensity treadmill exercise for 17 weeks. After this period of time, body composition and bone density were measured using dual-energy X-ray absorptiometry, and serum bone metabolism indicators were measured using an enzyme immunoassay. In addition, the bone microstructure was examined using micro-computed tomography and scanning of the femur, and femur proteins were subject to proteomic analysis. Results: Compared with the rats in the OVX group, the bone metabolism indicators in the OVX+EX group decreased significantly, femur bone density increased significantly, the number of the trabeculae increased, and continuity was higher. In the OVX+EX group, 17 proteins were significantly upregulated and 33 significantly downregulated. The main gene ontology and signaling pathways enriched by the proteins were identified as the tumor necrosis factor-mediated signaling pathways. The protein-protein interaction network identified the key proteins, and the correlation analysis of these proteins and the bone parameters found histone deacetylase 8(HDAC8) and leucine-rich transmembrane and O-methyltransferase domain containing (LRTOMT) and trimethylguanosine synthase 1(TGS1) and ankyrin repeat domain 46(ANKRD46) to be the key targets of exercise in relation to postmenopausal osteoporosis. Conclusion: Moderate-intensity treadmill exercise significantly improved the bone mass of OVX rats, and differentially expressed proteins, such as HDAC8 and LRTOMT and TGS1 and ANKRD46, could be the target of moderate-intensity treadmill exercise.